A Research Participant and End-User Approach to Research Collaboration and Co-Development in the Torres Strait. Issue 4 (December 2022) - Shibasaki, Sanchia; Harvey, A.; Mat, L. Ah; Lui, F. Watkin
Like many communities worldwide, those in the Torres Strait Islands face several severe social and environmental challenges. Torres Strait Islanders compete against the impacts of colonisation, globalisation and climate change to find sustainable solutions to ensure they survive and thrive in this rapidly changing world. This article describes the outcomes of workshops involving representatives from community-based non-government organisations on Thursday Island in the Torres Strait. It describes an approach to proactively kickstart research and identify grassroots innovations for complex social and environmental challenges. The findings suggest workshop participants obtained an increased awareness and understanding of research, the steps involved in research and their rights as participants. The researchers anticipate the findings from this project will contribute towards a better understanding of how to collaborate and co-develop research that is meaningful and beneficial to local contexts.